A Comparative ICF-CY–Based Analysis and Cultural Piloting of the Assessment of Preschool Children's Participation (APCP). (1st February 2015) - Nina, Kløve; Sigrid, Østensjø
ABSTRACT Aims: The aim of this study was to assess and compare the content and measurement construct of a new measure, the Assessment of Preschool Children's Participation (APCP), with other participation measures that have previously been linked to the ICF-CY, and pilot the APCP item relevance in a Norwegian context. Methods: All meaningful concepts in the APCP were linked to the ICF-CY and compared with the links of eight other preschool measures. The analysis of measurement construct was based on the attending/doing and involvement/engagement dimensions of participation. The pilot study was a survey among 36 parents of typically developing children. Results: Like most measures, the APCP has a relatively high content intensity on recreation and play, but differs by excluding self-care activities and including some learning activities. All instruments use objective indicators to measure participation. The APCP was not among the few that assessed subjective aspects of participation. The APCP items were found highly relevant in a Norwegian context, with the exception of a few organized activities taking place outside home environments. Conclusions: Differences in content and measurement constructs and the cultural equivalence should be considered when selecting a participation instrument for use among preschool children.